SSL-TLS security flaws : the BREACH and Logjam attacks - Ng, Christopher Bin Rui (Nanyang Technological University, 2021)
SSL, and its successor TLS, are protocols essential to the security of the modern web. They provide assurances that communications made using them are confidential (private), and that data integrity is maintained. Unfortunately, no protocol is without its flaws, and this is equally true for SSL/TLS.